Adhesive small bowel obstruction in a virgin abdomen in an elderly: a case report - Ismail, Althaf Adnan; Sasy, Ahmed Hegazy Mahdy; Saadullah, Mohamed Abdelraouf Hassan (International Surgery Journal, 2021)
Small bowel obstruction (SBO) is a major cause of morbidity and financial burden in hospitals around the world. Although adhesions account for more than 70% of SBO, they were thought to be less likely etiologies in a virgin abdomen. However, emerging evidence appears to challenge such a dogmatic approach. Here, we report a case of a 68 years old Maldivian man with a virgin abdomen who presented as small bowel obstruction secondary to de novo adhesions at terminal ileum. He was treated successfully with uneventful postoperative outcome in a government regional referral hospital.